PENGARUH PEMBEBANAN TERHADAP ARUS EKSITASI PADA GENERATOR - Helmizar; Hamdan Rizal Maulana; Agus Suandi (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2022)
The generator in the hydropower system is used to convert mechanical energy originating from the turbine rotation into electrical energy by producing an electromotive force. Excitation is one of the most crucial parts of the Generator system, where excitation plays a role in forming/producing electromagnetic flux, resulting in an induced emf. The amplifying current is used to adjust the magnitude of the output voltage according to the applied load. The tool used to regulate the excitation current is the Automatic Voltage Regulator (AVR). The differential loading on the generator changes every time. Therefore a power plant must be able to generate electricity in accordance with the magnitude of the changing load. In power generation, these loading fluctuations can be overcome by adjusting the water valve opening and the excitation current flowing to the electromagnet coil on the generator rotor with constant rotor rotation by the AVR so that electric power is generated according to the applied load. The purpose of this study is to analyze the effect of the load on the excitation current. The results obtained are the load has an effect on the excitation current.